(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Ovarian cystic masses are a common problem encountered in daily gynecological practice. Data reveals the prevalence of ovarian cyst vary widely. Reports suggest that between 8 and 18% of both premenopausal and postmenopsusal women have ovarian cyst. Most of the cysts are asymptomatic and discovered only in routine ultrasonography. Some of them are highly symptomatic hindering day to day activities of women. Symptoms depend to a large extent on the size of cysts. Modern management includes combined oral contraceptive pills and surgical management, if cysts continue to grow after 3 months of treatment. Since the oral contraceptive pills contribute many untoward effects, the need for alternative management especially in patients who wish to avoid surgical intervention is on high demand. Ayurveda addresses ovarian cyst under the broad classification of Granthi in which it can be correlated to Kaphaja Granthi in particular. A 27 year female patient married since 8 months, detected with Ovarian Cyst of size 6.6 x 6.1cm and complaining of severe lower abdominal pain, dyspareunia, bloating of abdomen, and burning micturition was treated according to Ayurvedic principles. Patient was given Kanchanara guggulu, Sukumaram kashayam, Guggulu panchapala churnam & Gomutra haritaki for a period of two months. Follow up USG showed complete disappearance of cyst and symptoms also subsided to a great extent. The present study emphasizes the role of Ayurveda in bringing a positive result in the management of ovarian cyst.